Performance of InGaN Light-Emitting Diodes Fabricated on Patterned Sapphire Substrates with Modified Top-Tip Cone Shapes - Hsu-Hung Hsueh; Sin-Liang Ou; Chiao-Yang Cheng; Dong-Sing Wuu; Ray-Hua Horng (International Journal of Photoenergy)
InGaN light-emitting diodes (LEDs) were fabricated on cone-shaped patterned sapphire substrates (PSSs) by using low-pressure metalorganic chemical vapor deposition. To enhance the crystal quality of the GaN epilayer and the optoelectronic performance of the LED device, the top-tip cone shapes of the PSSs were further modified using wet etching. Through the wet etching treatment, some dry-etched induced damage on the substrate surface formed in the PSS fabrication process can be removed to achieve a high epilayer quality. In comparison to the LEDs prepared on the conventional sapphire substrate (CSS) and cone-shaped PSS without wet etching, the LED grown on the cone-shaped PSS by performing wet etching for 3 min exhibited 55% and 10% improvements in the light output power (at 350 mA), respectively. This implies that the modification of cone-shaped PSSs possesses high potential for LED applications.